(untitled) (Medical Forum Monthly, 2025)
Objective: To detect the single nucleotide polymorphism rs2853669 in the telomerase reverse transcriptase promoter among patients' samples of papillary thyroid carcinoma and control samples, and then explore its correlation with specific clinicopathological parameters related to aggressive characteristics of papillary thyroid carcinoma. Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Department of Pathology & Forensic Medicine, Faculty of Medicine, AL Anbar University, Ramadi Iraq and University of Baghdad, Baghdad, Iraq. from 1st June 2022 to 30th June 2023. Methods: The samples collected were formalin-fixed paraffin-embedded tissue blocks from registered and stored cases of histologically proven papillary type thyroid carcinoma collected from the National Center for Education Laboratories, Medical City Campus - Baghdad and AL-Kimma private hospital. These tissue samples include 60 cases of papillary thyroid cancer and 15 cases of multinodular goiter. The telomerase reverse transcriptase promoter single nucleotide polymorphism rs2853669 was examined in 75 samples of papillary thyroid carcinoma and multinodular goiter, by real-time polymerase chain reaction subsequently correlating the findings with the clinicopathological features of papillary thyroid carcinoma, like age, sex, papillary thyroid carcinoma variants, size of the tumors, presence of capsules, multifocality, extrathyroid extension and lymph node metastasis. Results: The rs2853669 A˃G polymorphism was detected as AG genotype 40 (67%) the odd ratio was 1.111, p=0.0852 and confidence interval was (0.3658 to 3.3748), while GG genotype was evident in 14 of patients group (23%), the odd ratio was 0.687, P=0.567 and confidence interval was (0.1901 to 2.4864). The AA genotype wasevident in 6/60 (10%), the odd ratio was 0.22, p=0.022, and the confidence interval was (0.0503 to 0.7956.), Allele study, the most frequent allele in the patients' group was G allele 68 (57%), with a p-value of 0.0852. Regarding the correlation with clinicopathological parameters, multifocality is present in 52% of cases, with a p-value =0.05 Conclusion: The rs2853669 polymorphism is present in high rate(67% of AG genotype, and 23% in GG genotype) in patients with papillary thyroid carcinoma , and correlates significantly with multifocality.